Roles of microRNAs in metabolic reprogramming of breast cancer - Feng, Fan; Yu, Qingqing; Zhang, Feng (Journal of the Pakistan Medical Association, 2022)
Breast cancer cells exhibit deregulated metabolism. They require increased glucose uptake and glycolysis-associated enzymes to produce adenosine triphosphate by aerobic glycolysis rather than oxidative phosphorylation. Glutamine metabolism and fatty acid synthesis are also enhanced to meet the rapid and sustained cell growth. Triple-negative breast cancer and human epidermal growth factor receptor-2-positive breast cancers demonstrate significant metabolic reprograming with increased levels of glucose and glutamine metabolism. Increasing evidences also suggest that micro-ribonucleic acids play important roles in the regulation of metabolic enzymes of breast cancer cells in post-transcriptional manner. Human epidermal growth factor receptor-2 and oestrogen receptor signalling pathways could have crosstalk with micro-ribonucleic acids in metabolic regulation network. The current narrative review was planned to go through recent advances on the role of micro-ribonucleic acids on metabolic reprogramming in breast cancer cells. Key Words: Breast cancer, Phenotype, miRNA, Metabolic reprogramming, Glycolysis, Glutamine. Continuous...